FLOW PROPERTIES and TUBE FRICTION FACTOR of MILK CREAM: INFLUENCE of TEMPERATURE and FAT CONTENT - Flauzino, Rodrigo Diaz [UNESP]; Wilhelms Gut, Jorge Andrey; Tadini, Carmen Cecilia; Telis-Romero, Javier [UNESP] (Wiley-Blackwell, 2010)
The rheological behavior of milk cream was studied for different fat contents (0.10 to 0.31) and for a wide temperature range (2 and 87C) using a rotational rheometer. Newtonian behavior was observed, except for fat content between 0.20 and 0.31 and temperature between 2 and 33C, where viscoplastic behavior was remarkable. The rheological parameters (Newtonian viscosity, plastic viscosity and yield stress) and density were well correlated to temperature and fat content. Tube friction factor during flow of cream was experimentally obtained at various flow rates, temperatures and tube diameters (86 < Re < 2.3 x 104, 38 < Re(B) < 8.8 x 103, 1.1 x 103 < He < 6.7 x 103). The proposed correlations for density and rheological parameters were applied for the prediction of friction factor for laminar and turbulent flow of cream using well-known equations for Newtonian and viscoplastic flow. The good agreement between experimental and predicted values confirms the reliability of the proposed correlations for describing the flow behavior of cream.PRACTICAL APPLICATIONSThis paper presents correlations for the calculation of density and rheological parameters (Newtonian viscosity, Bingham plastic viscosity and yield stress) of milk cream as functions of temperature (2-87C) and fat content (0.10-0.31). Because of the large temperature range, the proposed correlations are useful for process design and optimization in dairy processing. An example of practical application is presented in the text, where the correlations were applied for the prediction of friction factor for laminar and turbulent tube flow of cream using well-known equations for Newtonian and viscoplastic flow, which are summarized in the text. The comparison with experimental data obtained at various flow rates, temperatures and tube diameters showed a good agreement, which confirms the reliability of the proposed correlations.